Uncovering the Leichhardt Superbasin and Kalkadoon-Leichhardt Complex in the southern Mount Isa Terrane, Australia - Olierook, Hugo; Mervine, E.M.; Armstrong, R.; Duckworth, R.; Evans, Noreen; McDonald, B.; Kirkland, Chris; Shantha Kumara, A.; Wood, D.G.; Cristall, J.; Jhala, K.; Stirling, D.A.; et al. (ELSEVIER, 2022)
The parts of the Mount Isa Terrane that crop out have been instrumental in deciphering the configuration of the supercontinent Nuna. In addition, these rocks host prolific base and precious metals. Further south, the Mount Isa Terrane is buried by >800 m of Phanerozoic cover that, to date, has primarily been investigated via geophysical surveys. Here, we present zircon U-Pb and Hf isotopic data of granitoids, metabasalts and metasedimentary rocks from seven >1 km deep drill holes that provide a window into the basement geology of the southern parts of the Mount Isa Terrane. The oldest rocks, intersected in two of the drill holes, are a series of granitic gneisses dated at ca. 1865 Ma, corresponding to the Kalkadoon-Leichhardt Complex. The majority of the encountered lithology in the drill holes are metasedimentary rocks with associated volcanic rocks and intruding granitoids, which bracket the remaining stratigraphy to ca. 1800–1760 Ma, corresponding to the lower and middle parts of the Leichhardt Superbasin. The ca. 1865 Ma Kalkadoon-Leichhardt Complex and ca. 1800 Ma granitoids have unradiogenic Hf isotopic signatures that necessitate an Archean lithosphere underneath the Mount Isa Terrane. Detrital zircon from the Leichhardt Superbasin may have been derived locally but also share age and Hf isotopic signatures with the eastern and northern Gawler Craton, implying possible long-distance transport. Metamorphic events recorded in discrete zircon grains and rims reveal punctuated tectonic activity at ca. 1760–1750 Ma and ca. 1720–1710 Ma in the southern Mount Isa Terrane, related to the pre-Wonga Event and the second stage of the Wonga Orogeny. The stratigraphy and events in the southern Mount Isa Terrane can be correlated to the northern and eastern Gawler Craton in South Australia, which may only have been ∼500–1000 km from the Mount Isa Terrane at the time of deposition. Ultimately, the results from these new drill holes reveal the extent of the Mount Isa Terrane under deep sedimentary cover and strengthen the links between the North and South Australian Cratons during the protracted assembly of the supercontinent Nuna.